Higher education in austerity Europe - Nixon, Jon (Bloomsbury Academic, 2017)
The financial crisis of 2007/2008 prompted governments across Europe to adopt austerity measures aimed at the reduction of their escalating budget deficits. Higher Education in Austerity Europe explores how the resulting cuts in public expenditure - together with the increasing reliance on the privatisation of services - have impacted on higher education directly through the reduction of public sector provision and indirectly as a result of the social and political consequences of that reduction. Moreover, it explores how the effects of these economic policies have differed markedly across the national regions of Europe, with the result that inequality has increased significantly both within and between national regions, and this, in turn, has led to social and political dislocation within and across communities. It is only by viewing higher education within this broader context that we can begin to understand the full implications of the austerity measures introduced over the last ten years. Jon Nixon draws together leading scholars to delve into the complexity of impact and response generated by these measures. Part 1 focuses on cross-European perspectives; Part 2 on the impact of austerity measures within national systems; and Part 3 on new perspectives and possibilities. The volume also includes considered responses from 'outsiders' by academics located in Asia, Australia, and the USA, providing an additional dimension to the analysis.